2014
DOI: 10.1177/0731948714525622
|View full text |Cite
|
Sign up to set email alerts
|

“Waiting to Fail” Redux

Abstract: This introduction to the special issue provides an overview of the promise, but also the ongoing challenges, related to Response to Intervention (RTI) as a means of both prevention and identification of reading disabilities. We conclude by describing the articles in this special issue and considering their implications for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, implementation of the response-to-intervention approach has not borne the anticipated fruit; children who fail to respond to well-founded intervention are just as likely to be identified following a comprehensive assessment with objective standards for referral for intervention as after their poor response to intervention – so why wait? Moreover, the characteristics of ‘treatment resistors’ include the phonological deficits that characterise dyslexia (Al Otaiba et al, 2014 ; Vellutino et al, 2004 ).…”
Section: Dyslexia Diagnosis and Treatmentmentioning
confidence: 99%
“…However, implementation of the response-to-intervention approach has not borne the anticipated fruit; children who fail to respond to well-founded intervention are just as likely to be identified following a comprehensive assessment with objective standards for referral for intervention as after their poor response to intervention – so why wait? Moreover, the characteristics of ‘treatment resistors’ include the phonological deficits that characterise dyslexia (Al Otaiba et al, 2014 ; Vellutino et al, 2004 ).…”
Section: Dyslexia Diagnosis and Treatmentmentioning
confidence: 99%
“…In contrast, RTI could reduce SLD identification in ways unrelated to improving academic outcomes. The RTI process could prolong the identification process through, for example, the length of time used to identify if students are responding to instruction (Al Otaiba et al, 2014; Hudson & McKenzie, 2016). Response to intervention requires that students are provided with effective instruction and have the opportunity to demonstrate that they have or have not benefited from this instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors concluded that two tiers of validated, highly aligned instruction were more effective than one. While researchers have begun to explore how Tier 1 practices may impact Tier 2 and 3 intervention effectiveness (Al Otaiba et al, 2014), more research is needed to better understand how variability in the quality of core instruction may differentially impact intervention outcomes.…”
Section: Tier 2 Interventions Within the Context Of Core Instructionmentioning
confidence: 99%